Game Edukasi Pengenalan Cerita Rakyat Lampung Pada Platform Android - Ardi Zulkarnais; Purwono Prasetyawan; Adi Sucipto (Politeknik Harapan Bersama, 2018)
Folklore is an oral tradition story passed down from generation to generation in the life of society. But today, folklore is less popular than abroad cinema which is packed with interesting form. In the Lampung region there is many people who do not know the folklore story about Lampung. In fact, folklore has a moral value, and also as a cultural heritage of the region. The purpose of this research is to design and build an educational game application of Lampung folklore to increase the interest of children and society to know and read Lampung folklore which is a cultural heritage that must be preserved. The development of educational folklore game application constructed from web and mobile platforms. The testing method that is done on aspects of Usability, Functionality, Portability, and Efficiency. Based on the results of usability testing on 5th and 6th grade elementary students using a questionnaire obtained 92.44% results, the functionality tested by 2 experts in the field of software engineering obtained 100% results, portability performed on the smartphone android version of gingerbread until marshmallow obtained 80% , and testing efficiency using Testdroid gets 15% average CPU usage results and an average memory of 175 MB.